2005
DOI: 10.1002/clc.4960280307
|View full text |Cite
|
Sign up to set email alerts
|

Losartan and end-organ protection-lessons from the renaal study

Abstract: Background: The Reduction in ENdpoints with the Angiotensin Antagonist Losartan (RENAAL) study reported that losartan delayed the progression of renal disease in patients with type 2 diabetes and nephropathy. Diabetic or renally impaired patients are at high cardiovascular risk, a risk potentially increased in patients with both conditions. Hypothesis: This post hoc analysis examined whether baseline proteinuria was predictive of cardiovascular outcomes, and whether losartan modifies the risk of cardiovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 30 publications
0
13
0
1
Order By: Relevance
“…tion Evaluation (HOPE) [6][7][8], Losartan Intervention For Endpoint reduction in hypertension (LIFE) [9,10], Reduction of Events with Angiotensin Converting Enzyme Inhibition (RENAAL) [11,12] and Irbesartan Diabetic Nephropathy Trial (IDNT) [13]. The ability of RAS inhibitors to mitigate cardiovascular risk is thought to be mediated, not only by their ability to lower blood pressure, but also by their inhibitory effects on atherosclerosis, left ventricular hypertrophy and renal damage in diabetic patients.…”
mentioning
confidence: 99%
“…tion Evaluation (HOPE) [6][7][8], Losartan Intervention For Endpoint reduction in hypertension (LIFE) [9,10], Reduction of Events with Angiotensin Converting Enzyme Inhibition (RENAAL) [11,12] and Irbesartan Diabetic Nephropathy Trial (IDNT) [13]. The ability of RAS inhibitors to mitigate cardiovascular risk is thought to be mediated, not only by their ability to lower blood pressure, but also by their inhibitory effects on atherosclerosis, left ventricular hypertrophy and renal damage in diabetic patients.…”
mentioning
confidence: 99%
“…It has been demonstrated that Ang II induces monocyte chemoattractant protein-1 (MCP-1) and interleukin-8 (IL-8) release via activation of the nuclear factor (NF)-ĸB pathway [1]. A large scale of clinical studies have demonstrated that blockade of Ang II by angiotensin-converting enzyme inhibitor (ACEI) or AT 1 receptor antagonist reduces the incidence of cardiovascular events in patients with hypertension, atherosclerosis (AS) and after myocardial infarction [2,3,4]. …”
Section: Introductionmentioning
confidence: 99%
“…; Viberti and Wheeldon ; Kowey et al. ). These studies also support the activated state of intrarenal RAS in the early stage of diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%